Development of Electropneumatic Simulation Learning Media based on Virtual Reality for Increasing Students' Competence Skills in Industrial Automation Engineering of Vocational School - Sugiarto, Hariyadi; Hatmojo, Yuwono Indro (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2024)
This research and development aim to (1) know the development step of Electropneumatic simulation learning media based on Virtual Reality for increasing students' competence skills in Industrial Automation Engineering; (2) create a proper Electropneumatic simulation learning media based on Virtual Reality for increasing students' competence skill in Industrial Automation Engineering; (3) analyze the effectiveness level of Electropneumatic simulation learning media based on Virtual Reality for increasing students' competence skill and response in Industrial Automation Engineering. This research and development used the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The effectiveness level of virtual reality media was analyzed using n-gain data from the pre-test and post-test enhancement score results. The results of this research and development are as follows: (1) the developed virtual reality media worked well after passing the functional test by using the Black Box testing method; (2) the development of the Virtual Reality learning media received an average score of 87.77% from three media experts and an average score of 88.75% from two subject matter experts. Based on these average scores, virtual reality learning media is categorized as